(untitled) (Itinera, 2024)
Within the historiographical and theoretical question of the relationship between aesthetics and rhetoric, according to which terms and concepts of aesthetics were also formed thanks to rhetoric, which circumscribes a perceptible and circumstantial sphere of reason, the present issue is dedicated to investigating a poietic idea of memory. Within this framework, the interest in memory and not imagination is legitimised precisely by the desire to analyse the productive capacity of rhetoric from the ’inferior’ faculty that seems at first glance the least creative, since traditionally memory has an accumulative and conservative function. Instead, our intention is precisely to suggest, thanks to the contributions published here, how memory is not simply a place of storage, but a source of invention. A memory that is therefore the very condition of the creative act and of the passage from the already known to the possible new. The issue is thus divided into two parts: the first deals with the specific topic of poietic memory, the second explores some aspects of the more general question of the relationship between aesthetics and rhetoric.